Literature Review on “Relationship to Knowledge”. Theoretical Movements and Possibilities of the Psychopedagogical Analysis in School Learning - Vercellino, Soledad (2015)
This literature review paper discusses the different theoretical movements that have arisen from the notion of “relationship to knowledge” in its effective use in empirical and theoretical research projects of different disciplines.  In the international academic community, numerous initiatives aim at addressing, from different disciplines, problems related to knowledge transfer and its appropriation relying on the heuristic power of the “relationship to knowledge” notion.  These initiatives include theoretical and empirical studies on the relationship of the school-related people to knowledge: teachers and students that enroll basically in two major schools –the psychoanalytic school of the Centre de Recherche Education et Formation (CREF), of the University of Paris X-Nanterre, created by Jacky Beillerot and continued by Nicole Mosconi and Claudine Blanchard-Laville; and the sociological school of the “Education, socialization, and local communities” (ESCOL) Group formed in 1987 in the Department of Education Sciences of the University of Paris VIII, Saint Denis, under the direction of Bernard Charlot–. There are evident efforts to clarify theoretically this notion. Researchers agree that the relationship of an individual to knowledge is based on two vital processes. The first one of these processes is related to the early relationships of children within the family, which provides certain characteristics to those relationships: somehow “enabling marks” printed by the subjectivity processes on the way in which the individual becomes related to knowledge. The second one is related to passing through exogamic institutions –e.g. education system, employment– which, with their own reservoir of meanings, operating logics, and demands to the individual would seem as an opportunity to shake, modify, or strengthen such relationship. Studies differ in the dimensions of the analysis: studies in the framework of ESCOL emphasize the meanings that individuals built around knowledge, their relationship to knowledge and, consequently, to school; studies in the framework of CREF are focused on certain unconscious phenomena: transferential, imaginary, or even instinctual phenomena. What is clear is the persistence of a theoretical-epistemological problem: the way of conceptualization of the individual and knowledge, and the relationship established by the syntagma between both.